Moringa Leaf Powder as Environmentally Friendly Repellent Agent for Controlling the Warehouse Insect Pest for Black Soybean Grain - Roosma Ria, Elly; Hidayat, Enceng; Muliani, Yenny; Komariah, Ai; Abdullah, Rohana; Masnenah, Endeh; Kantikowati, Endang (Jurnal Agrosci, 2024)
Black soybean grain (Glycine max L. Merril.) storage is susceptible to insect pests such as Callosobruchus analis (F.), which feeds on soybeans. Steroids/triterpenoids, phenolics, alkaloids, tannins, and terpenoids found in moringa leaf powder can be employed as insect repellents in black soybean grain warehouses. The purpose of this study was to ascertain how applying plant-based insecticides made from powdered moringa leaf will affect the amount of C. analis (F.) that died, the severity of the damage, and the weight loss of black soybean seeds of the Detam 4 Prida varieties. The study took place from August to October 2019 at an elevation of 878 meters above sea level in the Biology Laboratorium of the Agriculture Faculty, University of Winaya Mukti. An experimental design including five treatments and five replications was employed as the research methodology. A was not given any moringa leaf powder; B, C, D, and E each received 0.25, 0.75, and 1 grams of moringa leaf powder, fine powder, and so on. 10 pairs of C. analis (F) per jar were used in each treatment, which involved 100 g of black soybean grain. In the storage of black soybean grain, the percentage of seed damage, weight loss, the number of eggs, larvae, pupae, and images, and mortality of C. analis (F) were all impacted by 0.75 g of moringa leaf powder, according to the findings. According to this research, C. analysis, a warehouse insect pest, is effectively repelled by powdered moringa leaf (F.).